2008
DOI: 10.1016/j.bbmt.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of Hurler Syndrome after Stem Cell Transplantation

Abstract: Hurler syndrome (HS) is a severe inborn error of metabolism causing progressive multi-system morbidity and death in early childhood. At present, stem cell transplantation (SCT) is the only available treatment that can prevent central nervous system disease progression in HS patients. Although SCT has been shown to be effective for several important clinical outcome parameters, the reported clinical outcome after successful SCT is variable among HS patients and there are still some major limitations. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
168
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 102 publications
6
168
0
7
Order By: Relevance
“…These studies suggest that, when performed early enough in the disease process, HCT improved or stabilized neurocognitive development and adaptive skills in most children, particularly in combination with enzyme replacement therapy, preventing progressive deterioration (Malm et al 2008;Bjoraker et al 2006;Eisengart et al 2013). Nonetheless, the neurocognitive and adaptive outcomes after HCT for Hurler syndrome are highly variable (Aldenhoven et al 2008). Several factors are suspected to play a role in this heterogeneity, including genotype, age at transplantation, graft source, and demographic factors, but their relative contributions have been incompletely studied (Grewal et al 2003;Prasad and Kurtzberg 2010;Peters et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that, when performed early enough in the disease process, HCT improved or stabilized neurocognitive development and adaptive skills in most children, particularly in combination with enzyme replacement therapy, preventing progressive deterioration (Malm et al 2008;Bjoraker et al 2006;Eisengart et al 2013). Nonetheless, the neurocognitive and adaptive outcomes after HCT for Hurler syndrome are highly variable (Aldenhoven et al 2008). Several factors are suspected to play a role in this heterogeneity, including genotype, age at transplantation, graft source, and demographic factors, but their relative contributions have been incompletely studied (Grewal et al 2003;Prasad and Kurtzberg 2010;Peters et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There is consensus about the efficacy of HSCT when performed early in life for MPS-IH 9,13,14 and at early stages in CALD 6,7,12,15 . Case reports suggested that HSCT might reduce demyelination in juvenile (onset between two and 14 years) and adult forms of MLD when performed as early as possible 3,4,5,16 .…”
mentioning
confidence: 99%
“…Insufficient enzyme delivery to poorly vascularized tissues is thought to account for musculoskeletal deterioration after transplantation, similar to that of untreated children (Weisstein et al 2004;Aldenhoven 2008). Although HSCT may improve ventricular hypertrophy and ventricular function, cardiac valve disease persists , and hearing impairment, persistent corneal clouding, and noninfectious pulmonary complications (e.g., diffuse alveolar hemorrhage, idiopathic pneumonia syndrome) after transplantation are also common (Souillet et al 2003;Kharbanda et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since enzyme replacement therapy (ERT) is not capable of crossing the blood-brain barrier, HSC transplantation is the treatment of choice for Hurler syndrome. Clinical outcomes include reversal of organomegaly, preservation of neurocognitive development, and improved hearing, vision, and cardiopulmonary function in most transplanted patients (Guffon et al 1998;Whitley et al 1993;Shapiro et al 1995;Peters et al 1996;Vellodi et al 1997;Peters et al 1998;Souillet et al 2003;Aldenhoven et al 2008;Malm et al 2008). However, outcomes are highly variable, and manifestations in certain organ systems continue to progress.…”
Section: Introductionmentioning
confidence: 99%